Chemical Bath Deposition of NiOx‐NiSO4 Heterostructured Hole Transport Layer for Perovskite Solar Cells. Issue 11 (20th September 2022) - Shen, Benben; Chen, Mengjiong; Zhang, Fan; Liu, Da; Liu, Xinyi; Xie, Jin; Yang, Shuang; Hou, Yu; Yang, Hua Gui
Abstract : Herein, the scalable chemical bath deposited NiO x ‐NiSO4 heterostructured films are reported as the efficient hole transport layers (HTLs) in perovskite solar cells. The NiO x ‐NiSO4 films show excellent hole extraction ability and reduce interfacial charge recombination in solar cell devices. By using NiO x ‐NiSO4 HTLs, a high power conversion efficiency of 20.55% is obtained, which is about 12.23% greater than that of the pure NiO x transport layer. This study provides a simple solution‐processing route toward the large‐area production and fabrication of full inorganic transport layers for perovskite photovoltaics. Abstract : A NiO x ‐NiSO4 heterostructured layer is proposed through a chemical bath deposition technique for efficient perovskite devices. Perovskite solar cell devices based on NiO x ‐NiSO4 HTL yield a high power conversion efficiency of 20.55%, which is much higher than that of the pure NiO x ‐based HTL (18.31%).